Diocles of Carystus. a collection of the fragments with translation and commentary - Diocles, of Carystus. (Studies in Ancient Medicine, 2001)
Diocles of Carystus (4th century BCE), also known as \'the younger Hippocrates\', was one of the most prominent medical authorities in antiquity. He wrote extensively on a wide range of areas such as anatomy, physiology, pathology, therapeutics, embryology, gynaecology, dietetics, foods and poisons. In his writings, he betrays strong philosophical influence, and his views present striking connections with the Hippocratic Corpus, Plato, Aristotle and Theophrastus. The study of Diocles' ideas has long been hampered by the absence of a reliable collection of the remaining evidence. This book presents and discusses all the fragments and testimonies to Diocles' views. Following on from the first volume, which presented the Greek, Latin and Arabic sources with facing English translation, the second volume provides a commentary on the fragments and places them in their intellectual context.